Остеопороз: вплив віку, статі, ожиріння та цукрового діабету - Ларін, О. С.; Кирилюк, М. Л.; Третяк, О. Е.; Щекатурова, Л. В.; Гирявенко, О. Я.; Доготар, В. Б.; Бикова, А. Є. (Clinical Endocrinology and Endocrine Surgery, 2014)
This review summarizes the current data on about the etiology, pathogenesis, diagnosis of osteoporosis and its impact on the development of age, sex, obesity and diabetes mellitus.